Severe immune thrombocytopenic purple in children critical of SARS-CoV-2: Case report - Jesus Dominguez Rojas; Mariela Tello Pezo; Álvaro Coronado Muñoz; Giancarlo Alvarado-Gamarra; Kenny Chonlon Murillo (Open Journal of Pediatrics and Child Health - Peertechz Publications, 2021)
Idiopathic Thrombocytopenic Purpura (ITP) is caused by production of platelet autoantibody. Then ITP can be caused by various viral infections, including Human Immunodeficiency Virus (HIV), Hepatitis C Virus (HCV), cytomegalovirus, herpes simplex virus, Zika virus and others [1]. Episodes of ITP can range from mild to life-threatening. We reported a pediatric patient with positive molecular test to SARS-CoV-2 associated with severe thrombocytopenia, with active bleeding, not meeting criteria for PIMS, refractory to conventional treatment with immunoglobulin and corticoids for Idiopathic Thrombocytopenic Purpura. The purpose of reporting the case is to provide the hematological manifestations of the new SARS-CoV-2 virus. Idiopathic thrombocytopenic purpura, in our patient the possible cause is the new coronavirus.